Relationship between Developmental Language Disorder (DLD) and reading and writing difficulties: A two-phase longitudinal study - Andreu, Llorenç; Balboa, Raquel; Ahufinger, Nadia; Ferinu, Laura; Sanz-Torrent, Mònica (Revista de Investigación en Logopedia, 2025)
Acquiring reading and writing skills is one of the main challenges in children's development. Children with Developmental Language Disorder (DLD) are at a higher risk of experiencing difficulties in reading and writing compared to children with Typical Language Development (TD). This study analyzed the reading and writing difficulties of a group of children who had been diagnosed with DLD around two years earlier. A total of 58 bilingual Catalan-Spanish children, including 31 children with DLD and 27 children with TD, participated in a two-phases longitudinal study. At Phase 1, all participants were assessed in oral language and diagnosed as either DLD or TD. Around two years later, Phase 2, their reading and writing skills were evaluated. The results showed significant differences in reading and writing performance between children with DLD and those with TD. The DLD group exhibited a higher percentage of difficulties in reading accuracy and speed, as well as in spelling. Additionally, a higher percentage of children in the DLD group showed low performance in reading (56%) and writing (86%) compared to the DT group (13% and 29,2% respectively). It is crucial to implement intensive intervention programs focused on reading and writing skills in children with DLD to reduce their impact on academic performance.
Keywords: Developmental Language Disorder; DLD; dyslexia; dysgraphia; reading; writing